Ticagrelor in patients with stable coronary artery disease: a role in improving prognosis - T. N. Novikova (Российский кардиологический журнал, 2020)
The aim of this review was to study the evidence base for the efficacy and safety of the P2Y12 receptor blocker ticagrelor in combination with acetylsalicylic acid in patients with stable coronary artery disease and high and moderate risk of adverse cardiovascular events. Currently, the mortality rate of this category of patients remains high. Long-term dual antithrombotic therapy allows to improve the prognosis. Ticagrelor at a low dose (60 mg 2 times a day) in combination with acetylsalicylic acid in randomized clinical trials and an actual clinical practice has shown a beneficial effect on prognosis in stable coronary artery disease.